IMPLEMENTASI KONVENSI HAK ANAK DI INDONESIA DALAM MENANGANI KASUS PERNIKAHAN DINI DI MASA PANDEMIC - Wulandari, Tengku Maudi; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study explores UNICEF's implementation of the Convention on the Rights of the Child in addressing early marriage in Indonesia, particularly during the COVID-19 pandemic. Despite legislative changes through Law Number 16 of 2019, which raised the minimum age for marriage to 19, significant challenges remain. Factors such as poverty, unemployment, and school closures due to social restrictions have actually driven the rise in early marriage, particularly in Asia. This study reviews various efforts undertaken by UNICEF and the Indonesian government through policy analysis, formal education programs, gender equality advocacy, and the implementation of the National Strategy for the Prevention of Child Marriage (STRANAS PPA). The research focuses on how these interventions are implemented, the obstacles they face, and their effectiveness in reducing early marriage rates amidst the pandemic. The results show that although there has been a decline in the number of early marriages following the implementation of the new policy, serious obstacles remain. Lack of public understanding, weak law enforcement, and the socio-economic impact of the pandemic are key inhibiting factors. Therefore, this study recommends stronger collaboration between the government, child protection agencies, and communities to strengthen the protection of children's rights and create more effective strategies for preventing early marriage in the future. Keywords: Implementation, Convention on the Rights of the Child, Pandemic, Early Marriage.